Psychosocial safety climate and employees’ health: A multilevel study / Yulita - Yulita, - (2016)

(untitled)
The aim of this research was to examine the role of a specific organizational climate, psychosocial safety climate (PSC), and its effect on health-related outcomes (i.e., emotional exhaustion, and physical and psychological distress) and work-related outcomes (i.e., work engagement and workaholism) via job characteristics (i.e., job demands and job resources). In contrast to most studies and theories introduced in the Western context, this study was conducted in Malaysia, in order to obtain the non- Western perspective for a better understanding regarding the importance of good organizational climate (i.e., PSC). The current research utilized a multilevel survey study and a quantitative diary study to test a series of statistical and methodological approaches. A sample comprising police personnel and teachers was used in the study. The first study employed a multilevel cross-sectional approach and involved 58 departments (N = 909) from the Contingent Police Headquarters in Bukit Aman, Peninsular Malaysia. By utilizing hierarchical linear modeling software (HLM version 7.0 [HLM 7]) for analysis, the study found, at the group level, that PSC had a negative relationship on individuals’ physical health problems (i.e., headache, stomach ache, nausea, and sleep problems). The second study utilized a multilevel longitudinal study and was conducted among 392 police personnel (26 departments), matched across a gap of four months. Using HLM analysis, the study revealed between-groups moderated mediation effects linking PSC to job resources, work engagement, and workaholism, and, in cross-links, to psychological distress. The study also indicated that, at the group level, PSC improved the level of work engagement via job resources and mitigated the level of psychological distress over four months. iv The third and fourth studies employed a multilevel diary study which involved 23 schools in the State of Selangor, Malaysia (N = 109; diary data = 545 occasions). The diary study is a useful approach for capturing the fluctuation of everyday experiences within and between individuals in the work context. By employing HLM analysis, the third study revealed that the organizational level of enacted PSC (supervisor support) moderated the relationship between espoused PSC and daily emotional exhaustion. The research also found that enacted PSC (supervisor support) mediated the relationship between espoused PSC and daily work engagement. Finally, the fourth study revealed that 15% of the PSC variance was due to the school, 44% was due to between-persons PSC variance, and 41% was due to within-person PSC variance. This study indicates that PSC resides at all levels of analysis. Overall, the current study supports the notion of PSC’s primary and secondary roles, confirming that PSC is a leading indicator and a moderator of the relationships between job conditions and outcomes. Specifically, this study provides further insight regarding PSC from the Malaysian context by utilizing various work occupations and methods of data collection and, more importantly, using a multilevel approach in order to scrutinize several aspects related to work environment and individual work-related outcomes. The current research suggests that PSC is one of the appropriate strategies to target in order to improve the quality of the work environment and employees’ health and well-being.